Digital integration: a novel readout concept for XIDER, an X-ray detector for the next generation of synchrotron radiation sources - Fajardo, Pablo; Busca, P.; Erdinger, Florian; Fischer, Peter; Ruat, M.; Schimansky, David (Journal of Instrumentation, 2020)
This paper introduces the incremental digital integration concept, a novel readout scheme for the front-end of 2D pixelated X-ray detectors. The readout scheme includes features found in both current photon-counting and charge-integrating devices and is particularly suitable for detectors that need to operate with very high photon flux, under strong pileup conditions, and have to provide high sensitivity with noise-free effective operation. The core concept of this scheme is to slice the total exposure time required to acquire a given image in very short time intervals of the order of one microsecond or less that we call subframes. The detector signal is integrated for each subframe in the analog domain and digitised individually at the pixel level. This scheme allows to identify and discard those values for which the measured signal is only built from dark current or noise contributions. The final pixel value is then obtained in the digital domain by summing up the values of the non-discarded subframes. In the proposed scheme all this signal processing happens at pixel level in the detector front end. Reaching high dynamic range is not the only advantage of this method, digital integration offers the possibility of continuous cancellation of the dark current contributions even if they are not stable or fluctuate in time. This opens the possibility of building integrating detectors able to operate at high duty cycles, including continuous beam, with high-Z compound semiconductor sensors, a major challenge for the upcoming synchrotron radiation sources such as the ESRF Extremely Brilliant Source (EBS) currently under advanced construction that will become the first fourth-generation high-energy synchrotron facility worldwide. The XIDER detector, the first implementation of the incremental digital integration scheme, is planned to be a very fast and versatile high dynamic range detector optimised for high energy scattering and diffraction applications at ESRF-EBS and future similar facilities.